Comprehensive Evaluation of Water Resources on a Long Time Scale Based on Analytic Hierarchy Process - CHEN Hao; ZHANG Yimin; ZHANG Xiaolin; XIONG Jia; DONG Qianjin (Renmin Zhujiang)
On a long time scale,the comprehensive water resources in the water resources system is not only related to natural incoming water,but also greatly affected by the underlying surface and human activities.Therefore,on a long time scale,the comprehensive water resources change is affected by many factors and closely related to social development.However,there is no consensus on the current research on assessing changes in comprehensive water resources by multiple factors on a long time scale.This paper constructs a comprehensive water resource evaluation system with 10 indicators in terms of natural incoming water,comprehensive water use,and social factors by the analytic hierarchy process,calculates the water resources volume by taking the upper reaches of Hanjiang River Basin as an example,and concludes that the comprehensive water resources of this river basin fluctuate greatly inter-year,but generally show a downward trend,as well as classifies the state of comprehensive water resources into 5 types according to different score intervals,and on this basis,analyzes the development trend of comprehensive water resources in the upper reaches of Hanjiang River Basin.The results show that the comprehensive water resources in the upper reaches of Hanjiang River Basin will be at high shortage risk in the future,so it is necessary to take reasonable measures to improve water efficiency.